Derivation in English: Names of professions and their translation into Serbian - Ljubičić Gordana M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2018)
Derivation is one among the many processes of word-formation in English. It is a word-formation process by which a new word is produced from an already existing one by adding affixes (prefixes, infixes or suffixes) to a base. Affixes are also added to a base in the process of inflection, but in the case of inflection, it is not a new word that is produced, but only a grammatical variant of an already existing word. The paper discusses the affixes (suffixes mostly), which are used to produce the words denoting professions in English. It also deals with the new professions that are appearing every day due to the changes in all areas of human life and how the English language produces the new terms to cover these new needs. The point is that the names of all those professions are hard or even impossible to translate into Serbian, so the job of a translator is to discover the ways of how to find the best solution for the problem either by inventing a new term, or more often by adapting the foreign words to follow the rules of the Serbian language, which is not an easy task to do.